Research and Manufacture of Anti-rolling Torsion BarEquipment for CRH6 Inter-city EMUs - CUI Zhi-guo; ZOU Min-jia; LIU Wen-song; DU Fang-meng; CHENG Hai-tao (机车电传动)
CRH6 anti-rolling torsion bar equipment was introduced from operation principle, scheme design, stress analysis, stiffness calculation and strength analysis. Test results showed that the structure, stiffness, strength and manufacture technology of anti-rolling torsion bar could fully meet the operation requires; With 10 million times of fatigue tests, the device did not have any problems.